Methylglyoxal, a Reactive Glucose Metabolite, Induces Bladder Overactivity in Addition to Inflammation in Mice - Oliveira, Mariana G. de; Medeiros, Matheus L. de; Tavares, Edith B. G.; Mónica, Fabiola Z.; Antunes, Edson (Frontiers in Physiology, 2020)
Diabetic bladder dysfunction (DBD) is one of the most common complication of diabetes. Methylglyoxal (MGO), a highly reactive dicarbonyl compound formed as a by-product of glycolysis, is found at high levels in plasma of diabetic patients. Here, we explored the effects of chronic administration of MGO on micturition pattern (cystometry) and bladder contractility in vitro in healthy male C57/BL6 mice. Methylglyoxal was given at 0.5% in drinking water for 4 weeks. Exposure to MGO led to bladder tissue disorganization, edema of lamina propria, partial loss of urothelium and multiple leukocyte infiltrates. Filling cystometry revealed significant increases of micturition frequency and number of non-voiding contractions (NVCs) in the MGO group, clearly indicating an overactive bladder profile. Bladder contractions induced by electrical-field stimulation (EFS) and carbachol were significantly higher in the MGO group, while the muscarinic M2 and M3 mRNA expressions remained unchanged between groups. Additionally, MGO exposure induced upregulation of TRPA1 and down-regulation of TRPV1 and TRPV4 in bladder tissues. Methylglyoxal did not change the mRNA expression of the advanced glycation end products receptor (RAGE), but markedly increased its downstream NF-κB - iNOS signaling. The mRNA expression of cyclooxygenase-2 (COX-2) and reactive-oxygen species (ROS) levels remained unchanged. Altogether, our data show that 4-week MGO intake in mice produces an overactive bladder phenotype in addition to bladder inflammation and increased NF-kB / iNOS signaling. TRPA1 up-regulation and TRPV1 / TRPV4 down-regulation may account for the MGO-induced bladder overactivity. Scavengers of MGO could be an option to ameliorate bladder dysfunction in diabetic conditions.